A newly designed observation and response chart's effect upon adverse inpatient outcomes and rapid response team activity. Issue 8 (August 2016) - O'Connell, A.; Flabouris, A.; Kim, S. W.; Horwood, C.; Hakendorf, P.; Thompson, C. H.
Abstract : Background: Adverse inpatient events may diminish with earlier response to clinical deterioration. Observation and response charts with a tiered escalation response are recommended for use. Aims: To examine the impact of an observation and response chart and altered calling criteria on rapid response team (RRT) calls, cardiac arrests and intensive care unit (ICU) admissions from the ward and hospital deaths. Methods: Linked administrative and clinical data from an Australian, adult tertiary hospital for August 2007 to June 2013 (pre‐chart) and July 2013 to December 2014 (post‐chart) and analysed using interrupted time series analysis. Results: Pre‐chart RRT calls were increasing by 1.7 calls per 10 000 hospital admissions per month, whilst ICU admissions from the ward, deaths and cardiac arrests were decreasing by 0.3, 0.25 and 0.079 per 10 000 admissions per month respectively. Immediately upon chart introduction, the RRT call rate increased by 82% (66–98% CI; P  < 0.01), the ward admissions to ICU rate increased by 41% (14–67% CI; P  < 0.01) and the rates of deaths and cardiac arrests did not change. In the post chart period, both the pre‐chart increasing trend in the rate of RRT and decreasing trend in the rate of ICU admissions changed significantly to become constant. The pre chart trends in the cardiac arrest rate and hospital mortality did not change. Conclusion: Observation and response charts increased RRT and ICU workload without improving cardiac arrest rate or mortality. Future chart evaluation should identify features beneficial to patient outcomes and refine those that consume critical care resources that are not associated with improved patient outcomes.